LITERATURE REVIEW UNITED NATIONS AND INDONESIAN GOVERNMENT FOR MANAGEMENT DEFORESTATION CASES IN KALIMANTAN ISLAND - Nurul Hikmah (Jurnal PubBis, 2023)
For a long time the cause of deforestation in Indonesia, especially in Kalimantan island has invited several parties to take part in handling this deforestation cases. One of them is the Unites Nations or UN, it is known that the cause of deforestation in Indonesia is very worrying because it will have an impact on climate change, disaster nature and ect, that threatens the safety of humanity and nature. The UN unit collaborated with the government of Republic of Indonesia to follow up on this deforestation case. This study use qualitative research methods with a SLR approach based on a database that publishes articels in the form af accredited journals international. The aims of this study is to map the involvement of the UN in handling deforesttaion in Indonesia. The results is that REDD+ as ideal scheme from UN which must involve all stakeholders for manage forestry in Kalimantan Island, by involving local communiies, utilizing technology, as well as inter-sectoral coordination that must be improved. The existence of REDD+ which was coined by the UN and Indonesia together since 2010 and also other countries preserved nature and life in the forest in a sustainable mannner.